Profesionalisme Auditor terhadap Kualitas Audit pada Inspektorat Kabupaten Lombok Timur - Rusli Amrul; Baiq Kisnawati (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to examine the professional auditor by examining the effect of competence, independence and accountability on audit quality. This research was conducted at the Inspectorate of East Lombok Regency. The population in this study were auditor functional officers and P2UPD functional officers who were involved in inspection and supervision activities at the East Lombok Regency Inspectorate. Data were obtained by distributing 51 questionnaires to respondents who were at the Inspectorate of East Lombok Regency, 50 questionnaires were returned and could be used. Data using a partial test (t test). This test aims to find out individually (partial) the independent variable has an effect on the dependent variable. The results showed that competence, independence, and accountability had a positive effect on audit quality at the East Lombok Regency Inspectorate. The results of this study illustrate that the increase in professional competence, independence and accountability of auditors affects the quality of the resulting audit.